Influence of induction hardening residual stresses on rolling contact fatigue lifetime. (June 2022) - Areitioaurtena, Maialen; Segurajauregi, Unai; Fisk, Martin; Cabello, Mario J.; Ukar, Eneko
Abstract: Rolling contact fatigue is a unique mode of fatigue that components under cyclic contact loading experience. In this work, the impact of induction hardening residual stresses in rolling contact fatigue lifetime is investigated experimentally and numerically using the Dang Van multiaxial criterion. Various residual stress fields from induction hardening are simulated using the finite element method and are mapped into a classical mono-contact finite element model. The impact of induction hardened residual stresses on the lifetime of a component has been investigated, and the importance of incorporating the residual stress profile into fatigue life assessments is affirmed. Highlights: A life extension up to 156% can be achieved with compressive residual stresses. Larger residual stresses minimize damaged volume and damage initiation depth. Dang Van with orthogonal shear provides more accurate RCF prediction. A methodology to incorporate residual stresses into fatigue analyses has been developed. Selecting the right quenching medium can be critical for component performance.